(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
One of the factors shaping the high-tech structure of the state economy is the innovative retraining of highly educated and disciplined specialists. This article develops specific recommendations for training an educated and intellectually developed specialist, who is considered an important value and a decisive force in achieving the goals of modernization and renewal of all structures of society.